Development of the infant gut microbiome predicts temperament across the first year of life. (10th December 2022) - Fox, Molly; Lee, S. Melanie; Wiley, Kyle S.; Lagishetty, Venu; Sandman, Curt A.; Jacobs, Jonathan P.; Glynn, Laura M.
Abstract: Perturbations to the gut microbiome are implicated in altered neurodevelopmental trajectories that may shape life span risk for emotion dysregulation and affective disorders. However, the sensitive periods during which the microbiome may influence neurodevelopment remain understudied. We investigated relationships between gut microbiome composition across infancy and temperament at 12 months of age. In 67 infants, we examined if gut microbiome composition assessed at 1–3 weeks, 2, 6, and 12 months of age was associated with temperament at age 12 months. Stool samples were sequenced using the 16S Illumina MiSeq platform. Temperament was assessed using the Infant Behavior Questionnaire-Revised (IBQ-R). Beta diversity at age 1–3 weeks was associated with surgency/extraversion at age 12 months. Bifidobacterium and Lachnospiraceae abundance at 1–3 weeks of age was positively associated with surgency/extraversion at age 12 months. Klebsiella abundance at 1–3 weeks was negatively associated with surgency/extraversion at 12 months. Concurrent composition was associated with negative affectivity at 12 months, including a positive association with Ruminococcus-1 and a negative association with Lactobacillus . Our findings support a relationship between gut microbiome composition and infant temperament. While exploratory due to the small sample size, these results point to early and late infancy as sensitive periods during which the gut microbiome may exert effects on neurodevelopment.